SPIRITUALITY DIMENSIONS AND THE CARING NURSE-PATIENT INTERACTION SKILLS AMONG ASIAN STUDENTS - Maniago, J D (LIFE: International Journal of Health and Life-Sciences, 2017)
This study aimed to determine how the dimensions of spirituality intelligence affect the caring nurse-patient interaction skills of student nurses from three Asian countries. A descriptive correlation type of research was utilized with questionnaire in Google forms as the main instrument of this study. A total of 184 Asian student-nurses from Indonesia, Philippines and Singapore served as participants. Partial least square structural equation modeling was used to statistically analyze the data. Results of the structural model revealed that spiritual intelligence on the aspect of critical existential thinking is significantly related to the caring nurse-patient interaction skills in terms of humanism (β=0.164), helping relationship (β=-0.178), problem solving (β=0.131), and environment (β=.-0.538). Moreover, spiritual intelligence on the aspect of personal meaning production is significantly related to the caring nurse-patient interaction skills in terms of helping relationship (β=-0.154), problem solving (β=0.126) and needs (β=-0.174). It was also found out that the spiritual intelligence on the aspect of conscious state expansion is significantly related to the caring nurse-patient interaction skills in terms of humanism (β=-0.128), hope (β=0.197) and helping relationship (β=-0.149). Further analysis of the structural model revealed that the spiritual intelligence on the aspect of transcendental awareness is significantly related to the caring nurse-patient interaction skills in terms of problem solving (β=0.012) and spirituality (β=-0.246). It is recommended to mainstream spirituality in nursing education courses to foster a humanistic outlook in establishing a caring interaction between student nurses and the recipients of nursing care.